Studi Literatur Dampak Negatif Penggunaan Gadget terhadap Perkembangan Sosial Anak Usia Dini - Ficky Adi Kurniawan; Nakhma’ussolikhah (Sekolah Tinggi Ilmu Administrasi Yappi Makassar Jl. Sumba no 46, Kota Makassar, Sulawesi Selatan, 2025)
In today's digital era, it is difficult to separate gadgets such as smartphones, tablets, laptops, and other devices from everyday life. Although gadgets facilitate communication and facilitate access to information to support productivity and convenience, excessive or unwise use can cause various negative impacts on physical, mental, and social health. This study uses a literature review method to investigate the impact of gadget use on social development in early childhood. By analyzing secondary data from books, journals, articles, websites, and related research findings, the aim is to provide a comprehensive understanding of the negative impacts of gadget use on the social development of early childhood. The results show that the negative impacts of excessive gadget use in early childhood include social isolation, health problems, and an imbalance between physical and mental activity. It is very important for parents to actively monitor, and guide children's gadget use to prevent addiction and promote healthy development. By understanding the impact of gadget use, parents can apply the right parenting style and encourage positive social skills and reduce the risk of gadget addiction in the digital era.